1998
DOI: 10.1007/s002130050743
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the discriminative and antinociceptive effects of morphine and its glucuronide metabolites after central or systemic administration in the rat

Abstract: The potential of centrally (ICV) or systemically (SC) administered M6G to substitute for morphine in a drug discrimination task was characterized in the present study. Rats with a cannula in the lateral cerebral ventricle were trained to discriminate between injections of morphine (3 mg/kg, SC) and saline using a discrete-trial avoidance/escape procedure. Substitution tests were conducted with SC or ICV morphine, morphine-3-beta-D-glucuronide (M3G), or morphine-6-beta-D-glucuronide (M6G) and response latency i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Additional support for this conclusion includes the finding that M6G, like morphine, fully reproduced the DS effects of heroin in monkeys trained to discriminate heroin from vehicle (present study; Platt et al, 2001). M6G also has been found to reproduce the DS effects of morphine in rats trained to discriminate morphine from vehicle (Easterling and Holtzman, 1998). Shared DS effects may indicate pharmacological effects at a common site of action, implying that similar receptor populations mediate the DS effects of heroin, morphine, and M6G.…”
Section: Discussionmentioning
confidence: 88%
“…Additional support for this conclusion includes the finding that M6G, like morphine, fully reproduced the DS effects of heroin in monkeys trained to discriminate heroin from vehicle (present study; Platt et al, 2001). M6G also has been found to reproduce the DS effects of morphine in rats trained to discriminate morphine from vehicle (Easterling and Holtzman, 1998). Shared DS effects may indicate pharmacological effects at a common site of action, implying that similar receptor populations mediate the DS effects of heroin, morphine, and M6G.…”
Section: Discussionmentioning
confidence: 88%
“…It is reported that these metabolites are similarly produced in iv and sc administration and hepatic microsomes in rats (Kuo et al, 1991;Wu et al, 1997;Van Crugten et al, 1997;Ogura, 2000). In rats, M6G generalized to the discriminative stimulus effects of morphine, but not M3G (Easterling and Holtzman, 1998). This fact suggests that the morphine metabolite M6G is also related to the discriminative stimulus effects of morphine.…”
Section: Discussionmentioning
confidence: 95%
“…The sc morphine generalized to the training dose of morphine at 3 mg/kg, and the po morphine generalized at 10-fold this dose level (30 mg/kg). In discrimination training, sc morphine at 3 mg/kg is a commonly used route and dose combination, as is ip administration at this dose (Nishida et al, 1989;Easterling and Holtzman, 1998;Li et al, 2013). This means that sc morphine at 3 mg/kg induces sufficient discrimination stimulus effects.…”
Section: Discussionmentioning
confidence: 99%
“…In a drug discrimination procedure, M6G was fully substituted for heroin in rhesus monkeys [ 184 ] and for morphine in rats [ 185 ]. In the latter study, M6G was 17 times more potent than morphine when these drugs were administered in the cerebral ventricles, but less potent when injected subcutaneously.…”
Section: Neurobehavioral Effects Of Heroin and Its Metabolitesmentioning
confidence: 99%